MOTIVASI BELAJAR MAHASISWA PENDIDIKAN MATEMATIKA UIN ALAUDDIN MAKASSAR DALAM MENGGUNAKAN MEDIA E-LEARNING GOOGLE MEET DAN ZOOM CLOUD MEETING - Wahyuni; Fitriani Nur; Andi Halimah; Nidya Nina Ichiana; Ahmad Farham Majid (Faculty of Tarbiyah and Teacher Training, 2022)
This study aims to describe the learning motivation of students who are taught using e-learning media in the form of google meet and zoom cloud meetings. This research is a type of descriptive research, which was carried out at UIN Alauddin Makassar. The population in the study were all students of Mathematics Education Batch 2017-2020 at UIN Alauddin Makassar with a research sample of 69 people. The research instrument used was a student learning motivation questionnaire. Data analysis in this study uses descriptive statistics. The results of this study revealed that the learning motivation of students who were taught using e-learning media in the form of Google Meet was in the medium category with an average score of 77.71, while the learning motivation of UIN Alauddin Makassar students who were taught using e-learning media in the form of zoom cloud meeting is in the medium category with an average score of 76.14. Therefore, the two e-learning media are recommended for online learning.